Corticospinal excitability of the soleus muscle during water immersion - Mujunen, Toni (2019)
Water-based exercising is a common form of physical activity used in both rehabilitation and athletic training. However, despite being widely used its’ effects on neuromuscular control is poorly understood. Therefore, the main aim of this study was to investigate how a brief (15 min) immersion to thermoneutral (34°C) water would affect corticospinal excitability and/or intracortical circuitry when soleus muscle is targeted, compared to dry land measures. The experiments were conducted with the subject either resting (passive experiment) and separately during a low-level submaximal (20% of maximal voluntary contraction) isometric voluntary contraction (active experiment) while seated. The depth of immersion was at sternum level.